Teacher pedagogical training: experience from Brazil and Uruguay - Xavier., Amanda Rezende Costa; Carrasco., Bueno; Azevedo., Maria Antonia Ramos de [UNESP]; Maldonado., Elaine Cristina; Antonello., Jaqueline [UNESP] (Univ Republica, Comision Sectorial Ensenanza, 2023)
The present work is concerned with presenting, from an institutional perspective, the actions of teacher pedagogical training in a Bra-zilian and a Uruguayan institution. The challenge of teaching qualification in higher education is a contemporary theme that has mobilized institutions concerned with assuming the teacher training process as part of the excellence of this level of education. In the light of the theoretical framework of university pedagogy, the article is guided by a qualitative approach, based on a multiple case study methodology (Yin, 2001) that compares two experiences related to the same pillar: the offer of pedagogical training with a view to pro-moting professional development teacher. The clipping is based on an experience in Uruguay, whose data were collected in 2019, and an experience in Brazil, whose data refer to the 2020-2022 period. The results indicate that both experiences contemplate, institutionally, the valuation of training spaces, and converge in actions related to advisory work in the collective dimension of teaching. However, they present different investments associated with the maintenance of these training spaces, thus constituting different processes that trigger the professional development of the teachers involved.
Keywords: teacher professional development; didactic-pedagogical training; higher education teacher; university pedagogy; university pedagogical advisor